Adult Intussusception due to Gastrointestinal Stromal Tumor: A Rare Case Report, Comprehensive Literature Review, and Diagnostic Challenges in Low-Resource Countries. (6th August 2018) - Ssentongo, Paddy; Egan, Mark; Arkorful, Temitope E.; Dorvlo, Theodore; Scott, Oneka; Oh, John S.; Amponsah-Manu, Forster
Abstract : We present a rare case of gastrogastric intussusception due to gastrointestinal stromal tumor (GIST) and the largest comprehensive literature review of published case reports on gastrointestinal (GI) intussusception due to GIST in the past three decades. We found that the common presenting symptoms were features of gastrointestinal obstruction and melena. We highlight the diagnostic challenges faced in low-resource countries. Our findings emphasize the importance of early clinical diagnosis in low-resource settings in order to guide timely management. In addition, histological analysis of the tumor for macroscopic and microscopic characteristics including mitotic index and c-Kit/CD117 status should be obtained to guide adjuvant therapy with imatinib mesylate. Periodic follow-up to access tumor recurrence is fundamental and should be the standard of care.